How People Recognize Dark Pattern in E-Commerce? - Hafidza Safara Zahratunnisa; Imairi Etiveni; Betty Purwandari; Erisva Hakiki Purwaningsih (Jurnal Sistem Informasi, 2025)
In the digital era, many manipulative design tactics, commonly referred to as ‘dark patterns’, have emerged. These tactics are designed to hide, mislead, deceive, and even exploit users while using an application. This study explores the dynamics of user perception and their ability to recognize these dark patterns. The study involved evaluating 11 participants through in- depth interviews and exposure to 12 screenshots from Indonesian e-commerce platforms containing these design tactics. Not all participants were able to recognize dark patterns in the screenshots. Those who were able often attributed their awareness to personal experience, highlighting the importance of experiential learning in identifying and understanding deceptive interface elements. However, factors such as unclear interface information, user trust in the interface, and the blending of marketing strategies with dark patterns contribute to the difficulty users experience in recognizing these manipulative tactics. Beyond Indonesia, the findings of this study have broader implications for countries with similar digital ecosystems or socio- economic contexts. Understanding how dark patterns are perceived by users in Indonesia can provide valuable insights for countries with comparable characteristics, particularly in terms of digital literacy levels, trust in online platforms, and regulatory frameworks, where similar manipulative tactics may be prevalent, necessitating a focus on improving understanding of manipulative tactics when interacting with e-commerce applications. This analysis underscores the urgency of increasing user awareness to prevent fraud in design manipulation in e- commerce applications, thereby avoiding user harm. The implications of this study advocate a focus on improving understanding of manipulative tactics when interacting with e-commerce applications, urging digital product practitioners to apply ethical and transparent design principles to improve user satisfaction. There is a need for stricter regulations and clear guidelines to protect consumers from unethical manipulative tactics.